2021
DOI: 10.1016/j.neulet.2020.135423
|View full text |Cite
|
Sign up to set email alerts
|

Post-weaning social isolation increases ΔFosB/FosB protein expression in sex-specific patterns in the prelimbic/infralimbic cortex and hippocampus in mice

Abstract: Social isolation is a growing public health concern across the lifespan. Specifically, isolation early in life, during critical periods of brain development, increases the risk of psychiatric disorders later in life. Previous studies of isolation models in mice have shown distinct neurological abnormalities in various regions of the brain, but the mechanism linking the experience of isolation to these phenotypes is unclear. In this study, we show that ΔFosB, a long-lived transcription factor associated with ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Older women are also more likely to be socially isolated based on census data demonstrating that, compared to men, women live alone more frequently [ 34 ]. In addition to higher risk for exposure to social isolation and loneliness in women, animal models suggest long-standing sex-dependent effects on abnormal gene expression in the brain related to neurological dysfunction [ 74 , 88 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…Older women are also more likely to be socially isolated based on census data demonstrating that, compared to men, women live alone more frequently [ 34 ]. In addition to higher risk for exposure to social isolation and loneliness in women, animal models suggest long-standing sex-dependent effects on abnormal gene expression in the brain related to neurological dysfunction [ 74 , 88 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the largest remaining questions about the SI phenotype is how an organism translates the experience of SI stress to the observed behavioral effects. A previous study from our group [15] focused on the molecular effects of adolescent SI and found that the transcription factor ΔFosB was upregulated in SI males. Those findings about ΔFosB combined with the behavioral effects in this study are new pieces of the potential biological pathway between SI stress and the observed changes.…”
Section: Behavior Effects In the Greater Context Of Adolescent Si Effectsmentioning
confidence: 99%
“…Interestingly, postnatal days 21-35 is a period of significant amounts of social play behavior in mice and isolation during this period can lead to deficits in social interactions in adulthood [13,14]. Moreover, the social behavior deficits are directly related to abnormal interneuron function in the prefrontal cortex [14] We previously reported that SI during the 21-35 day period is associated with increased levels of ΔFosB, a transcription factor associated with chronic stress [15]. ΔFosB has also been implicated in studies of reward-seeking behavior [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Social isolation-induced stress impacts behavior. Prolonged social isolation in adulthood enhances the motivational value and anticipatory behaviors of a social encounter 10 , increases social interactions 11 , and impairs social memory 12 , 13 . Adult isolation can impair novel object recognition, induce territorial behaviors, and alter anxiety-like and risk assessment behavior in the open field 14 .…”
Section: Introductionmentioning
confidence: 99%